The challenges and perspectives of introducing online media subscriptions in Serbia - Nedeljković Marko (CM. Communication and Media)
Despite the global trend of online media subscriptions, no daily in-formative online media in Serbia has begun charging for access to its digital content. The "Online Media and Subscription in Serbia in 2023" research study, conducted in October of last year, revealed that mistrust and low-quality media content are the biggest obstacles to the introduction of online media subscriptions in our country. The study found that 46.3% of respondents do not believe in what online media in Serbia publish. However, the research also identified a significant base of potential subscribers, with 31.8% of respondents who are intensively, regularly and occasionally informed in online media indicating their willingness to pay for access to domestic digital editions in the near future if they were offered content they perceive as worth paying for. This paper highlights the key reasons why online media subscriptions have yet to take off in our country, then the potential for charging digital content from the audience in Serbia, as well as the characteristics of media content for which the audience would be most willing to pay in the event of subscription introduction.